Agricultural Jiaosu: An Eco-Friendly and Cost-Effective Control Strategy for Suppressing Fusarium Root Rot Disease in Astragalus membranaceus - Gao, Youhui; Zhang, Yue; Cheng, Xiaoqian; Zheng, Zehui; Wu, Xuehong; Dong, Xuehui; Hu, Yuegao; Wang, Xiaofen (Frontiers in Microbiology, 2022)
Root rot caused by the pathogenic fungi of the Fusarium genus poses a great threat to the yield and quality of medicinal plants. The application of Agricultural Jiaosu (AJ), which contains beneficial microbes and metabolites, represents a promising disease control strategy. However, the action-effect of AJ on Fusarium root rot disease remains unclear. In the present study, we evaluated the characteristics and antifungal activity of AJ fermented using waste leaves and stems of medicinal plants, and elucidated the mechanisms of AJ action by quantitative real-time PCR and redundancy analysis. The effects of AJ and antagonistic microbes isolated from it on disease suppression were further validated through a pot experiment. Our results indicate that the AJ was rich in beneficial microorganisms (Bacillus, Pseudomonas, Lactobacillus, etc.), organic acids (acetic, formic, and butyric acids, etc.) and volatile organic compounds (alcohols, esters, etc.). It could effectively inhibit F. oxysporum and the half-maximal inhibitory concentration (IC50) was 13.64 %. The antifungal contribution rate of the microbial components of AJ reached 46.48 %. Notably, the redundancy analysis revealed that the Bacillus and Pseudomonas genera occupied the main niche during the whole inhibition process. Moreover, the abundance of the Bacillus, Pseudomonas and Lactobacillus genera were positively correlated with the pH-value, lactic, formic and butyric acids. The results showed that the combined effects of beneficial microbes and organic acid metabolites increased the efficacy of the AJ antifungal activity. The isolation and identification of AJ’s antagonistic microbes detected 47 isolates that exhibited antagonistic activities against F. oxysporum in vitro. In particular, B. subtilis and B. velezensis presented the strongest antifungal activity. In the pot experiment, the application of AJ and these two Bacillus species significantly reduced the disease incidence of Fusarium root rot and promoted the growth of Astragalus. The present study provides a cost-effective method to control of Fusarium root rot disease, and establishes a whole-plant recycling pattern to promote the sustainable development of medicinal plant cultivation.